Experimental test of predation's effect on divergent selection during character displacement in sticklebacks - Rundle, Howard D. (National Academy of Sciences, 2003)
Ecological character displacement is common in nature but the mechanisms causing divergence are not well understood. The contributions of ecological interactions other than competition have received little attention. We conducted a pond experiment to explore the contribution of both competition and predation to character divergence in threespine stickleback species. We estimated the strength of divergent selection on a morphologically intermediate target population between competition treatments under two alternate predation treatments. Divergent selection on the target population tended to be stronger in the predator-addition treatment than in the predator-reduction treatment, a difference that approached significance (P = 0.09). This trend occurred even though competition was strongest in the predator-reduction treatment. Overall, the strength of divergent selection was best predicted by stickleback mortality (P = 0.025) being strongest where mortality was highest. These results indicate that predation and other agents of mortality can enhance the rate of change in competition per unit of phenotypic divergence and, thereby, divergent selection, even as they lower the overall strength of competition. In this way, predation and other agents of mortality may facilitate, rather than hinder, character displacement.